Knowledge and Attitude Evaluation of Using Cintronella Products For Dengue Hemorrhagic fever Prevention of Citizen in Bang Khanoon, Bang Kruai District, Nonthaburi Province - Sajjatham, Nontri (National Interest, 2021)
The purpose of this research aims to 1) knowledge and attitude evaluation of people who using citronella extracts for Dengue Hemorrhagic Fever prevention in Bang Khanoon sub-district, Bang Kruai District, Nonthaburi Province 2) relationship between bio social factors and people who using citronella extracts for Dengue Hemorrhagic Fever prevention 3) relationship between acknowledgement and attitude evalutiont of people who using citronella extracts for Dengue Hemorrhagic Fever prevention. The samples were 186 citizens in Bang Khanoon sub-district, Bang Kruai District, Nonthaburi Province. The research instrument was questionnaires and statistics for data analytics are frequency distribution, percentage, mean, standard deviation, chi-square, pearson’s correlation coefficient, multiple regression analysis and content analysis from in-depth interview form for the 8 village committees. The research findings were summarized as follows: 1) knowledge about using citronella extracts for Dengue Hemorrhagic Fever prevention have high level at 83.87%. Attitude about using citronella extracts for Dengue Hemorrhagic Fever prevention have moderate level at 50.54% and high level at 40.86%. Behavior about using citronella extracts for Dengue Hemorrhagic Fever prevention have moderate level at 47.31%, 2) relationship between age and occupation with about using citronella extracts for Dengue Hemorrhagic Fever prevention have significant level ≤ 0.05 and 3) knowledge about Dengue Hemorrhagic Fever and herbs against mosquitoes positively correlated with using citronella (r=0.012) there was not statistically significant and relationship between attitude of using citronella extracts to mosquitoes carrier safeguard in Dengue Hemorrhagic Fever prevention there was statistically significant positive relationship (r=0.386) at the level ≤ 0.05………………………………….